Can Pulsed Electric Fields Treated Algal Cells Be Used as Stationary Phase in Chromatography? - Pleissner, Daniel; Smetana, Sergiy (Frontiers in Sustainable Food Systems, 2022)
Microalgae are utilized for various purposes through cell content extraction and application. Cell walls are not utilized and not studied in an extensive manner. At the same time, composed of multilayer and fibrillar structures with various chemical compositions depending on microalgae species, they present an interesting object for chromatography. However, it requires the application of novel processing technologies (like Pulsed Electric Fields) able to selectively permeabilize the cell walls with pores of various sizes and shapes. Current review indicates the potential of microalgae cells walls application for separation by size exclusion, ion-exchange and hydrophobic interaction chromatography. However, such a hypothesis should be further experimentally proven.